The dual-field-of-view polarization lidar technique: a new concept in monitoring aerosol effects in liquid-water clouds - case studies - Jimenez, Cristofer; Ansmann, Albert; Engelmann, Ronny; Donovan, David; Malinka, Aleksey; Seifert, Patric; Wiesen, Robert; Radenz, Martin; Yin, Zhenping; Buehl, Johannes; Schmidt, Joerg; Barja Gonzalez, Boris; et al. (My University, 2020)
In a companion article (Jimenez et al., 2020), we introduced a new lidar method to derive microphysical properties of liquid-water clouds (cloud extinction coefficient, droplet effective radius, liquid-water content, cloud droplet number concentration N-d) at a height of 50-100 m above the cloud base together with aerosol information (aerosol extinction coefficients, cloud condensation nuclei concentration N-CCN) below the cloud layer so that detailed studies of the influence of given aerosol conditions on the evolution of liquid-water cloud layers with high temporal resolution solely based on lidar observations have become possible now. The novel cloud retrieval technique makes use of lidar observations of the volume linear depolarization ratio at two different receiver field of views (FOVs). In this article, Part 2, the new dual-FOV polarization lidar technique is applied to cloud measurements in pristine marine conditions at Punta Arenas in southern Chile. A multiwavelength polarization Raman lidar, upgraded by integrating a second polarization-sensitive channel to permit depolarization ratio observations at two FOVs, was used for these measurements at the southernmost tip of South America. Two case studies are presented to demonstrate the potential of the new lidar technique. Successful aerosol-cloud-interaction (ACI) studies based on measurements with the upgraded aerosol-cloud lidar in combination with a Doppler lidar of the vertical wind component could be carried out with 1 min temporal resolution at these pristine conditions. In a stratocumulus layer at the top of the convective boundary layer, we found values of N-d and N-CCN (for 0.2 % water supersaturation) ranging from 15-100 and 75-200 cm(-3), respectively, during updraft periods. The studies of the aerosol impact on cloud properties yielded ACI values close to 1. The impact of aerosol water uptake on the ACI studies was analyzed with the result that the highest ACI values were obtained when considering aerosol proxies (light-extinction coefficient alpha(p)(ar) or N-CC(N)) measured at heights about 500 m below the cloud base (and thus for dry aerosol conditions).
Keywords: Depolarization ratio; Liquid water content; Effective radius; Cloud base; Cloud height; Cloud condensation nuclei; Extinction (optical mineralogy)